The Photo- and Phonosensitivity Avoidance Behavior Scales: Evaluating Clinical Utility in Pediatric Primary Chronic Headache - Allison M. Smith; Megan N. Silvia; Hannah Rogan; Alyssa A. Lebel (Children)
Background/Objectives: Pediatric primary chronic headache disorders are often associated with sensitivities to light (photosensitivity) and sound (phonosensitivity) that may trigger or worsen headache pain. These sensory sensitivities may result in changes to activity participation or environmental modifications to avoid visual and auditory stimuli. Over time, avoidance behaviors can inadvertently increase functional disability, suggesting the importance of their thorough consideration. The PhotoSensitivity and PhonoSensitivity Avoidance Behavior Scales (PHOTO-SABS and PHONO-SABS, respectively) were recently developed and preliminarily validated to assist clinicians in evaluating such behaviors. This study aimed to confirm each of their factor structures in a new sample and enhance their clinical utility. Methods: A sample of 176 youth (aged 8–17) with a primary chronic headache diagnosis completed the PHOTO-SABS and PHONO-SABS as part of their multidisciplinary evaluation in a pediatric headache clinic. Results: Consistent with the previous validation, confirmatory factor analyses supported a two-factor model for the PHOTO-SABS and a single-factor model for the PHONO-SABS. Tertile groupings (low, moderate, high) provided the most appropriate clinical reference points. The relative change criterion (RCCrit) was established at 6.4 points for both measures. Conclusions: These findings confirm that the PHOTO- and PHONO-SABS are psychometrically robust tools for clinicians to evaluate sensitivity-related avoidance behavior and to monitor response to interventions in youth with primary chronic headaches.